Buying Voters - M. Iqbal Fardian (Advanced Studies on Socio-Economy Development, 2021)
Political transaction has become a common phenomenon that accompanies elections. It does not only occur in countries with well-established democratic systems, but also in developing nations. Academic engagement with the concept of democracy increasingly explores its links to the chaotic commodification of electors' votes. Political transactions can trigger several problems, such as political structures, citizenship awareness, or cultural relations issues that form a democratic structure of the country. Political transactions are processes of negotiation that take place between elites. This paper explores the contestation of social positions to gain electors' votes in the context of the legislative election conducted in Banyuwangi. The strategies used by legislative candidates to obtain votes through transactional relationships demonstrates the various actors involved in general elections. First, the researcher argues that democratization has transformed the sacred position of the elites, especially the religious elite. Second, the complexity of relations between elites presents the position of a broker, which emphasizes the character of democracy in Indonesia, which is marked by issues of clientelism. Thus, it is essential to observe Indonesia's political praxis from the institutional practice point of view and its social problems that distort democratic values. Keywords: Clientelism, Transaction Cost Politic, Money Politics